Design Modeling and Aerodynamic Optimization of a Micro-Scale 3-Blade HAWT Wind Turbine at Tip Speed Ratio (λ= 6) - Saidah, Andi; Darman, Yahadi (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study investigates the geometric design and performance estimation of a micro-scale three-blade Horizontal Axis Wind Turbine (HAWT) using a Computer Aided Design (CAD) approach operating at a tip speed ratio (TSR) of λ = 6. The study focuses on low wind speed characteristics obtained from field measurements in the range of 3–8 m/s with an average speed of approximately 5–6 m/s. Micro wind turbines operating under these conditions often experience low aerodynamic efficiency due to low Reynolds numbers and fluctuating airflow. The research methodology includes determining initial turbine parameters with a rotor diameter of 1.5 m, parametric blade modeling using CAD software, and performance estimation using theoretical wind energy equations involving wind power, tip speed ratio, and power coefficient (Cp). Design adjustments were conducted by modifying blade chord distribution, twist angle, and pitch angle to achieve stable performance at TSR = 6. The results indicate that the estimated power coefficient increases from approximately 0.28 in the initial configuration to about 0.35–0.38 after geometric adjustment. The turbine is estimated to produce theoretical power in the range of 90–150 W under moderate wind conditions. The three-blade configuration with gradual twist distribution and moderate pitch angle improves aerodynamic stability and energy conversion efficiency. This study provides a CAD-based design framework for micro-scale HAWT turbines intended for low wind speed environments, particularly in urban coastal areas where wind potential is limited.